Analisis Prosedur Pemberian Kredit Usaha Rakyat (Kur) Bagi Nasabah Pada Pt. Bank Sumut Kcp Sei Sikambing - Rejeki Sihombing, Poppi Sry; Manurung, Amran; Lumbangaol, Manatap Berliana (CV. ITTC INDONESIA, 2025)
Every bank has a series of stages or procedures for granting credit that must be followed, starting from the submission of an application, analysis of customer eligibility, approval, disbursement of funds, to monitoring and collection. However, not all customers understand the established procedures, and this can be an obstacle for the bank. This study aims to analyze the procedures for granting People's Business Credit (KUR) at PT. Bank Sumut KCP Sei Sikambing, covering the stages of application submission, file investigation, credit analysis, decision making, contract signing, realization, and fund distribution. The analysis also highlights the differences in implementation between the types of KUR, namely Super Micro KUR, Micro KUR, and Small KUR. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The data is analyzed descriptively to obtain a real picture of the implementation of the KUR granting procedure in the field. The results of the study show that the KUR provision procedure at PT. Bank Sumut KCP Sei Sikambing has been implemented in accordance with applicable regulations, with adjustments to documents and depth of analysis based on the type of KUR. Credit distribution data for the 2022-2024 period shows an increase in the amount of credit distributed from IDR 87,343,404,765 to IDR 137,662,417,902, accompanied by a decrease in the non-performing loan (NPL) ratio from 1.34% to 0.43%. This reflects the effectiveness of the implementation of procedures and the success of the principle of prudence. Overall, it can be said that PT. Bank Sumut KCP Sei Sikambing has implemented KUR lending procedures effectively, in a structured manner, and with the principle of prudence. The procedures that are carried out carefully support more targeted KUR distribution and maintain the quality of the bank's credit.